Microbial Community Structure Along a Horizontal Oxygen Gradient in a Costa Rican Volcanic Influenced Acid Rock Drainage System - Arce-Rodríguez, Alejandro (2020)
We describe the geochemistry and microbial diversity of a pristine environment that resembles an acid rock drainage (ARD) but it is actually the result of hydrothermal and volcanic influences. We designate this environment, and other comparable sites, as volcanic influenced acid rock drainage (VARD) systems. The metal content and sulfuric acid in this ecosystem stem from the volcanic milieu and not from the product of pyrite oxidation. Based on the analysis of 16S rRNA gene amplicons, we report the microbial community structure in the pristine San Cayetano Costa Rican VARD environment (pH = 2.94–3.06, sulfate ~ 0.87– 1.19 g L−1, iron ~35–61 mg L−1 (waters), and ~ 8–293 g kg−1 (sediments)). San Cayetano was found to be dominated by microorganisms involved in the geochemical cycling of iron, sulfur, and nitrogen; however, the identity and abundance of the species changed with the oxygen content (0.40–6.06 mg L−1) along the river course. The hypoxic source of San Cayetano is dominated by a putative anaerobic sulfate-reducing Deltaproteobacterium. Sulfur-oxidizing bacteria such as Acidithiobacillus or Sulfobacillus are found in smaller proportions with respect to typical ARD. In the oxic downstream, we identified aerobic ironoxidizers (Leptospirillum, Acidithrix, Ferrovum) and heterotrophic bacteria (Burkholderiaceae bacterium, Trichococcus, Acidocella). Thermoplasmatales archaea closely related to environmental phylotypes found in other ARD niches were also observed throughout the entire ecosystem. Overall, our study shows the differences and similarities in the diversity and distribution of the microbial communities between an ARD and a VARD system at the source and along the oxygen gradient that establishes on the course of the river.